Design of Earthquake Detection Devices - Nuryaningsih, Rintania Eliyanti; La Baraja, Iswan; Sardju, Achmad P. (Program Studi Teknik Elektro Universitas Khairun, 2025)
Earthquakes are natural disasters that occur suddenly and can cause severe impacts, both in terms of structural damage and human casualties. To reduce the risks and consequences, an early warning system that provides rapid and accurate alerts is highly needed. This research aims to design and develop a simple yet effective earthquake detection device by utilizing the ESP32 microcontroller as the central processing unit. The system is equipped with an ADXL335 accelerometer sensor, which is capable of detecting vibrations or changes in acceleration along three main axes: X, Y, and Z. The sensor reads seismic activity and transmits the data to the ESP32 for real-time processing. When the detected vibration exceeds a predefined threshold, the system automatically activates a buzzer as an alarm and turns on three red LEDs as visual indicators. Each LED represents a level of earthquake intensity: mild, moderate, and strong. With these indicators, users can immediately recognize the severity of the earthquake and take prompt safety measures. The ESP32 not only processes data but also regulates the system’s responses to operate efficiently. This device is designed for use in households or other small-scale environments, offering advantages such as low cost, easy installation, and the use of commonly available components. Therefore, this system is expected to serve as an alternative solution that contributes to enhancing community preparedness against earthquake hazards.